Effect of famotidine on the pharmacokinetics of apixaban, an oral direct factor Xa inhibitor - Upreti VV; Song Y; Wang J; Byon W; Boyd RA; Pursley JM; LaCreta F; Frost CE (Dove Medical Press, 2013)
Vijay V Upreti,1 Yan Song,1 Jessie Wang,2 Wonkyung Byon,3 Rebecca A Boyd,3 Janice M Pursley,4 Frank LaCreta,1 Charles E Frost1 1Clinical Pharmacology and Pharmacometrics, Discovery Medicine and Clinical Pharmacology, 2Exploratory Development Global Biometric Sciences, Bristol-Myers Squibb, Princeton, NJ, 3Primary Care Clinical Pharmacology, Pfizer, Groton, CT, 4Analytical and Bioanalytical Department, Bristol-Myers Squibb, Princeton, NJ, USA Background: Apixaban is an oral, selective, direct factor Xa inhibitor approved for thromboprophylaxis after orthopedic surgery and stroke prevention in patients with atrial fibrillation, and under development for treatment of venous thromboembolism. This study investigated the effect of a gastric acid suppressant, famotidine (a histamine H2-receptor antagonist), on the pharmacokinetics of apixaban in healthy subjects. Methods: This two-period, two-treatment crossover study randomized 18 healthy subjects to receive a single oral dose of apixaban 10 mg with and without a single oral dose of famotidine 40 mg administered 3 hours before dosing with apixaban. Plasma apixaban concentrations were measured up to 60 hours post-dose and pharmacokinetic parameters were calculated. Results: Famotidine did not affect maximum apixaban plasma concentration (Cmax) or area under the plasma concentration-time curve from zero to infinite time (AUC∞). Point estimates for ratios of geometric means with and without famotidine were close to unity for Cmax (0.978) and AUC∞ (1.007), and 90% confidence intervals were entirely contained within the 80%–125% no-effect interval. Administration of apixaban alone and with famotidine was well tolerated. Conclusion: Famotidine does not affect the pharmacokinetics of apixaban, consistent with the physicochemical properties of apixaban (lack of an ionizable group and pH-independent solubility). Apixaban pharmacokinetics would not be affected by an increase in gastrointestinal pH due to underlying conditions (eg, achlorhydria), or by gastrointestinal pH-mediated effects of other histamine H2-receptor antagonists, antacids, or proton pump inhibitors. Given that famotidine is also an inhibitor of the human organic cation transporter (hOCT), these results indicate that apixaban pharmacokinetics are not influenced by hOCT uptake transporter inhibitors. Overall, these results support that apixaban can be administered without regard to coadministration of gastric acid modifiers. Keywords: apixaban, factor Xa inhibitor, famotidine, H2-receptor antagonists, hOCT inhibitor, drug–drug interaction